Fffect of Sulpher Application on Performance of Fiber Yield Difference Jute Varieties - Tripathi, Santosh Raj; Gupta, Binod Kumar; Karki, Sujan; Adhikari, Nirmala (Journal of Nepal Agricultural Research Council, 2025)
Jute, a cornerstone of Nepal’s agro-economy known as the "golden fiber," has faced a catastrophic decline in cultivated area and productivity. This decline is largely driven by degraded soil fertility in the intensive growing belts of the Terai region. Among essential nutrients, sulfur (S) has been identified as a critical limiting factor. Sulfur is vital for jute’s unique physiology, directly influencing the biosynthesis of fiber-strengthening compounds and lignin-cellulose metabolism. The objective of this study was to determine the optimal sulfur application rate for maximizing the growth, fiber yield, and quality of commercially important jute varieties. A two-year field experiment (2022–2023) was conducted at the Jute Research Program, Itahari, to evaluate the effects of graded sulfur application (0, 10, 20, 30, and 40 kg S ha⁻¹) on growth, yield, and fiber quality of four commercially grown jute varieties (Itahari-4, JRO-204, NJ-7010, Itahari-2). The experiment was arranged in a split-plot design with three replications. Observations included plant height, basal stem diameter, green plant yield, green fiber yield, dry fiber yield, dry stick yield, and fiber thickness. The experimental results indicated that there were no significant differences in basal diameter and fiber thickness traits across the tested combinations. These traits remained largely unaffected by sulfur, suggesting genotypic stability. However, sulfur application significantly enhanced plant height, green fiber yield, dry fiber yield, green stick yield and dry stick yield in the 30 kg S ha⁻¹ dose producing the highest overall performance across most traits. Among varieties, NJ-7010 (Rani) consistently exhibited superior growth and yield, particularly under optimal sulfur nutrition. The study concluded that 30 kg S ha⁻¹ is the optimal sulfur dose for improving jute productivity and fiber quality under Nepalese Terai conditions, and integrating responsive varieties with balanced sulfur fertilization could provide a cost-effective strategy to revitalize the declining jute sector.